2019
DOI: 10.5530/pj.2019.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Olea europaea and Its Constituents Promote Bone Health by Enhancing Osteoblast Differentiation and Proliferation: A Review

Abstract: Background: The human bone is in a constant state of balance between bone resorption and bone formation, maintained by the osteoclasts and osteoblasts respectively. Association of Mediterranean diet and bone health has been prevalently studied in recent years. Olive and its constituents have been suggested to be the major contributor to the benefits of the Mediterranean diet in bone health. Method: In this review, cellular and molecular mechanism of bone homeostasis and the influence of olive and its constitue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…In a study by Venäläinen et al (2006), an increased concentration of metabolizable P in the feed increased the crude ash content and the Ca and P content in the tibia of broilers. However, other components may also contribute to bone health, such as n-3 fatty acids (Liu et al, 2003) and polyphenols, which are present in Olea europaea L. by stimulating bone formation and inhibiting bone resorption, as they are thought to promote osteoblast differentiation and proliferation (Idrus and Saim, 2019). Several studies have shown that olives and their compounds can affect bone formation, maintain healthy bones and can be used as an effective dietary supplement in the treatment of osteoporosis, osteoarthritis, osteopenia and cartilage injuries (Đudarić et al, 2015;Hagiwara et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Venäläinen et al (2006), an increased concentration of metabolizable P in the feed increased the crude ash content and the Ca and P content in the tibia of broilers. However, other components may also contribute to bone health, such as n-3 fatty acids (Liu et al, 2003) and polyphenols, which are present in Olea europaea L. by stimulating bone formation and inhibiting bone resorption, as they are thought to promote osteoblast differentiation and proliferation (Idrus and Saim, 2019). Several studies have shown that olives and their compounds can affect bone formation, maintain healthy bones and can be used as an effective dietary supplement in the treatment of osteoporosis, osteoarthritis, osteopenia and cartilage injuries (Đudarić et al, 2015;Hagiwara et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Fe, Cu, Zn) and form indigestible complexes that reduce the absorption and thus the utilization of minerals (Yang and Landau, 2000;Sandberg, 2002;Surai, 2014). However, according to the results of numerous in vitro studies on human models investigating the effects of olive polyphenols on osteoblast differentiation and osteoporosis prevention, olive polyphenols can have a beneficial effect especially when bone homeostasis is disturbed, because they increase bone formation and inhibit its resorption (García-Martínez et al, 2014;Idrus and Saim, 2019;Melguizo-Rodríguez et al, 2018;Santiago-Mora et al, 2011).…”
Section: Abmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in phytomedicine have reported various health-promoting effects of olive oil and its extracts [1][2][3][4]. Olive oil contains numerous phytochemicals/phenolic compounds such as oleuropein, tyrosol, and hydroxytyrosol that are known to have potent antioxidant and cardio-neuroprotective effects [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%